Detection and phylogenetic analysis of blood-associated pathogens from spleen samples of wild raccoons (Procyon lotor) in Germany - Maria Sophia Unterköfler; Aria Schwingshandl; Barbara Eigner; Jutta Pikalo; Josef Harl; Joachim Spergser; Peter Steinbach; Diana Jeschke; Michael Striese; Elisabeth Striese; Hermann Ansorge; Hans-Peter Fuehrer; et al. (Scientific Reports)
Abstract Raccoons (Procyon lotor) originated in North America and have been introduced to Europe. Due to their close contact with human settlements, they are important reservoirs for zoonotic pathogens, such as Baylisascaris procyonis. The relevance and prevalence of vector-borne pathogens have not yet been fully elucidated. In this study, we screened 285 spleen samples of raccoons, collected between 2019 and 2022 in Germany. The samples were analysed by PCR to detect Mycoplasma spp., Anaplasmataceae, Bartonella spp., Babesia spp., Rickettsia spp., Filarioidea, Trypanosomatida and Hepatozoon spp., and positive PCR products were sequenced. In total, 104 samples were positive for Mycoplasma spp. (36.49%), making this the first study to detect Mycoplasma spp. in raccoons outside of North America. Three samples were positive for Babesia spp. (1.05%) and two for Anaplasma phagocytophilum (0.7%). Phylogenetic analysis revealed that the Mycoplasma spp. detected all belong to the haemotrophic mycoplasmas cluster and were grouped within a single phylogenetic clade. Two different Babesia spp. were detected, one of which was closely related to Babesia canis, while the other was more closely related to Babesia sp. from ruminants. It is unclear whether the pathogens detected have an impact on the health of raccoons or whether they may serve as a reservoir for other animals.